Sistema tributário brasileiro e os mercados "não convencionais": a legalização dos cassinos como fonte de arrecadação tributária - Albuquerque, Marcus Vinicius da Anunciação (2022)
This paper sought to analyse the potential for tax collection of casinos for Brazil, from an analysis of the brazilian tax system, in which a need for newer means of income to increase tax revenue has been observed, and the legalisation of casino gambling could provide such an opportunity. Throughout this text, two analysis were conducted; one focusing on the the economical impact such activities bring to countries in which they are allowed, as well as bills of law that seek to authorise the legal exercise of casinos in Brazil. Casinos are know to gather entertainmnet-focused gambling, and so, the leaders of many different countries saw an opportunity to raise their tax resources, since these places already generated jobs and promoted local tourism. Though in Brazil, this process was the inverse, as in 1946, it was made illegal by a presidential decree. Analysing the Country's current economic scenario, and the yields and benefits that gambling brings to places where it is legal, it is interesting to analyse the proposals regarding the legalisation of casinos that are being processed in Congress